The archival geographies of twentieth-century internationalism: Nation, empire and race. (January 2021) - Hodder, Jake; Heffernan, Michael; Legg, Stephen
Abstract: This paper argues that more explicitly geographical methodologies are required to study twentieth-century internationalism, which invite different conversations between international historians and historical geographers. We show how the form and location of international archival records is itself evidence of multiple, interlocking modes of internationalism which unevenly intersected with national, imperial, and pan-national pasts. This is explored through three case studies: the archive of the International Institute of Intellectual Cooperation (IIIC), located in the UNESCO headquarters in Paris; the Maharaja Ganga Singh Archive in the Indian city of Bikaner; and the papers of Lydia Brown in New Bedford, Massachusetts, a translator and interpreter at the Second Pan-African Congress. We argue that bringing the archives of large international organisations into dialogue with a wider overlooked field of international archival evidence offers new perspectives on what internationalism was, where it happened, and to whom it mattered. Highlights: Recent research on internationalism invites interrogation of archival sources. The form and location of records is evidence of transnational interactions. The archive reveals how internationalism was conceptually ambiguous. International pasts intermingle with national, imperial and pan-national records. Archives challenge what and where internationalism was and to whom it mattered.